Monitoramento e controle de emissão de material particulado em uma fonte estacionária - Almeida Filho, Francisco de (2008)
The goal of this study was the monitoring of emissions by sources in Lower Furnace Production of Iron-alloy and Steam Generators of Industry Production of Alcohol. This tracking emission of pollutants was conducted after the equipment of Control Issue performed by Filters in a Bag House in the Iron-alloy Industries Washers and in a Scrubber in Alcohol Industries. The sampling of material was accomplished through Isokinetic Collector Sample using the Isokinetic Collector of Atmospheric Pollutants (CIPA) which allows the sampling of representative quantity of gas flow and retention this material in absolute Particulate filter. Sampling and analysis of gas was made at same time using an Electrochemical Gas Analyzer for determining the levels of carbon monoxide, carbon dioxide, oxides of nitrogen and oxygen present in the effluent gas. In the Iron-alloy Industry the effectiveness of the control of particulate matter inside of the Bag House was at safe levels and given the specifications of Environmental Quality. Other relevant factor to the maintenance of good level of control was the efficiency of the Gases Cooling System which allowed the safe working of the Bag House without fluctuations in temperature that could put at risk the constituent material of the fabric filters and also using a Program for Preventive Maintenance System for Control of the Emissions keeps it was in perfect conditions of operation and avoiding defects or failures in controllers environmental. In the Sugar and Alcohol Industry you can see the System Control that must meet the limits imposed by regional bodies through control of emissions standards and limits still needs of improvements to decrease emissions within the new concept of cleaner production. Finally it finds that the emissions are presented with the values of issuing measured within the limits allowed by the Environmental Bodies. Its systematic monitoring will allow the maintenance of results within the environmental parameters which one can achieve higher levels of environmental control through reventive measures and monitoring.